Family Perceptions of a Cooking and Nutrition Program for Low-Income Children and Adolescents - Amy Saxe-Custack PhD, MPH, RD; Mallory Goldsworthy MPH; Heather Claire Lofton PhD; Mona Hanna-Attisha MD, MPH; Onyinye Nweke MD (SAGE Publishing, 2021)
Background . Flint Kids Cook, a nutrition and culinary program for children and adolescents, was created in October 2017 to address health concerns among youth and families in a low-income, urban community. In this study, researchers examined family experiences with the 6-week, chef-led program, which was taught in a farmers' market kitchen. Methods . At the conclusion of each session, researchers used an open-ended focus group format to assess program experiences, perceived impact on youth self-efficacy for cooking and healthy eating, and caregiver support. This qualitative study was guided by thematic analysis. Results . Between November 2017 and December 2018, 72 caregivers (n = 38) and students (n = 34) participated in separate focus groups. Caregivers were primarily female (74%) and African American (71%). Most students were African American (76%) and half were female. Recurrent themes included food acceptance, dietary modifications, confidence in the kitchen, and program design. Caregivers and students agreed that location and design of the program alongside facilitation by an experienced chef were important factors for program success. Conclusions . This study demonstrated that a chef-led healthy cooking program for youth was effective in improving perceived food acceptance, dietary habits, and confidence in the kitchen. The program could be modeled in similar communities to address diet and health of children and adolescents.